Hepatitis B viremia manifesting as polyarteritis nodosa and secondary membranous nephropathy - Balwani, Manish Rameshlal (J Nephropharmacol, 2016)
Renal involvement in hepatitis B-polyarteritis nodosa (HBV-PAN) usually occurs in the form of hypertension, microscopic hematuria, proteinuria but nephrotic range proteinuria or renal failure is very uncommon. A 60-year-old man had abdominal pain for 15 days which was followed by bilateral pedal edema in a day and in next three days he had sudden onset bilateral foot drop with numbness. He had weight loss of 10 kg in last 20 days. Pedal edema was pitting, bilateral. Macular skin rashes around both ankles were present. Serum creatinine was 2.4 mg/dl and blood urea nitrogen was 102 mg/dl.24 hour proteinuria was 3.4 g/day. Serum HBsAg, HBeAg and anti-HBc IgM were positive. Serum HBV-DNA level (PCR) was 582917 copies/ml. The nerve conduction study showed axonal and demyelinating polyneuropathy in bilateral lower limbs. A kidney biopsy revealed membranous nephropathy (MN). Doppler for renal vessels was normal. Prednisolone (60 mg/day), plasmapheresis (5 courses) and entecavir (0.5 mg/ every second day) were started. At 2 months follow up, patient improved in the form of grade 3/5 power in both lower limbs with sensory improvement. Twenty-four hours proteinuria decreased to 800 mg/day and serum creatinine reached to 1.5 mg/dl. Polyarteritis nodosa was due to HBV infection, but the etiology of MN was uncertain, as it has rarely been described in PAN. Proteinuria responded to nucleoside analogue therapy. So patient was considered to have an association of classic PAN and MN, both related to HBV. Patient responded to combined treatment of steroid, plasmapheresis and nucleoside analogue.